Teaching programming through specialized educational software and conversational agents - Ayala Cadena, Omar (2023)
Daily learning activities generate exchanges of ideas, doubts, and explanations between students and teachers. These dialogues and the possibility of asking a teacher questions disappear after classes. New automated communication tools developed with word processing programs, such as chatbots, have proven helpful in commerce and customer service. Some educational institutions are currently exploring the benefits of these programs in student care. This paper describes an exploratory study on the use of educational software and conversational agents in the teaching of programming; the objective is to identify the potential of this type of program to support teachers in the training of programmers and the accompaniment of students in their self-managed learning.